Inclusive Islamic Education (PAI) Learning Based on Developmental Differentiation: Strategies for Slow Learners and Gifted Learners - Zulfa Uswatun Hasanah; Eva Latipah nusa (Insight School Academy, 2026)
Introduction to the Problem: The increasing diversity of students’ developmental characteristics presents challenges for implementing inclusive Islamic Education (PAI), particularly in addressing the learning needs of slow learners and gifted learners. Purpose: This study aims to analyze the developmental characteristics of both groups from a developmental psychology perspective and to formulate a conceptual framework for inclusive PAI based on differentiated instruction. Design/Methods/Approach: Using a qualitative library research design, data were collected from academic books, scholarly journal articles, and relevant educational policy documents and analyzed through content analysis. Findings: The findings indicate that slow learners and gifted learners demonstrate distinct cognitive, social, and learning characteristics that require different instructional responses. These differences underline the importance of differentiated instruction throughadjustments to learning content, processes, and products. The study proposes a conceptual frameworkconsisting of developmental assessment, learning-needs mapping, differentiated instruction, and an inclusivelearning environment as interconnected components in inclusive PAI. Originality/Value: As a conceptualstudy, the proposed framework requires further empirical validation. This study contributes to theintegration of developmental psychology and inclusive pedagogy in PAI and provides a foundation fordeveloping learning practices that are more responsive to students’ developmental diversity.